Chubby but cheery? Investigating the compensatory judgments of high, medium, and low status weight groups in Malaysia - Wong, Kang Xin (2016)
We examined two strategies that people use in their social judgements – indifference and compensation. Given their average position we reasoned that an indifference strategy would characterise perceivers’ competence vs. warmth judgements of members of intermediate status groups because they do not possess features that deviate from normality. In contrast, high and low status groups deviate from normality, and we reasoned that an attention to the negative aspects of their competence vs. warmness should enlist a complimentary desire to compensate such groups in the opposite dimension, in line with societal norms of politeness. Results from Study 1 showed mixed support for these assumptions: Compensation was used for underweight faces (intermediate group) and ideal weight faces (high status), while an indifference strategy was used in the judgements of the overweight (low status) which we reasoned may be tied to cultural and individual differences. When these noise were removed in Studies 2a and 2b, we showed, consistent with our assumptions that the indifference strategy was used in the evaluations of the underweight (intermediate status), while compensation was used for the ideal-(high status) and over-weight (low status) categories. Finally, Study 2b showed that norms of politeness predicted the use of compensation, but only for the overweight low status category.